If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + 9j = 46 Solving 19 + 9j = 46 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 9j = 46 + -19 Combine like terms: 19 + -19 = 0 0 + 9j = 46 + -19 9j = 46 + -19 Combine like terms: 46 + -19 = 27 9j = 27 Divide each side by '9'. j = 3 Simplifying j = 3
| ln(x)=85.3 | | 8y+16=8y+20 | | 60/90 | | 7=2/5b-5 | | -7x-5(5x+14)=-6 | | (4b^2)^-1/2 | | S^2+8s-5=0 | | x-(x*0.55)=13548479*0.55 | | 1.5×45/2 | | 7y-3x=2 | | 1/3×3(5x-14)=18×1/3 | | x-(x*.2)=15668730*0.2 | | x-(x*0.2)=100*0.2 | | 5t-13=7 | | x-x*0.2=100*0.2 | | 6e+2=10e+4e | | 6x-5y=-60 | | 7x-16+5x-3+4x+7=180 | | (4x-1)(2x+4)=0 | | 11x-5+9x+1+3x=180 | | 7.3=p+0.1 | | p+1.5=1.6 | | 5.5=r-7.1 | | f(x)=x^4-4x^3-2x^2+12x+9 | | 3(4x+3)=-0(-x+2) | | Ll2c-7/3=5 | | 6x+4(-3x+31)=58 | | (16-2x)(12-2x)=0 | | 2logx-3logy+2logxy= | | -28=x-46 | | C=20n | | (2y)-x=50 |